TRANSFORMASI SISTEM PEMBINAAN SISWA: INTEGRASI PENDIDIKAN KARAKTER ISLAM DAN PENDEKATAN KINDNESS STRATEGY SEBAGAI SOLUSI ATAS DAMPAK NEGATIF REWARD DAN PUNISHMENT DI SMP MUHAMMADIYAH 4 GIRI - Mochammad Taufik Yunus; Hasan Basri (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
Dependence on reward and punishment systems in shaping student behavior remains a significant issue in modern education, particularly at the junior secondary level. This study aims to explore the implementation of the Kindness Strategy in the guidance and counseling process as an alternative method to foster student integrity through Islamic character education at SMP Muhammadiyah 4 Giri. A qualitative descriptive method was used, employing data collection techniques such as observation, in-depth interviews, and documentation involving school counselors, Islamic education teachers, and students from grades VII to IX. Findings indicate that many students display psychological symptoms such as anxiety, social withdrawal, and reliance on external validation, which hinder the development of intrinsic motivation and moral self-awareness. The Kindness Strategy—rooted in Islamic values such as Tazkiyatun Nafs (soul purification) and Akhlakul Karimah (noble character)—offers a humanistic and empathetic approach through reflective practices (muhasabah), structured habits, supportive social interactions, and emotional reinforcement. The transformation identified includes increased self-awareness, responsibility, and empathy among students. This suggests that character development based on kindness and Islamic values is more sustainable than behavior models driven by fear or material rewards. The study emphasizes the importance of integrating the Kindness Strategy into Islamic character education as a transformational approach to nurture morally upright and emotionally resilient students.